1977
DOI: 10.1021/ac50012a026
|View full text |Cite
|
Sign up to set email alerts
|

Theory of error in factor analysis

Abstract: Hg-Ni OTTLE at this pH, showing that the glyoxylic acid wave is obscured by hydrogen evolution at this electrode. As a result of the extended negative range, glyoxylic acid could be analyzed by thin-layer coulometry and by thin-layer differential pulse voltammetry in the Hg-Au OTTLE (26, 27).Reduction of Metals. The utility of the Hg-Au minigrid for the reduction of metal ions to the elemental form is limited by the tendency of the gold which is dissolved in the mercury film to form intermetallic compounds wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
115
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(119 citation statements)
references
References 26 publications
4
115
0
Order By: Relevance
“…These treatments are based e.g. on 2D correlation analysis (2DCOR) [22,23], mowing windows 2D concept (MW2D) [24,25], factor (FA) and principal component analysis (PCA) [26][27][28][29], etc.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These treatments are based e.g. on 2D correlation analysis (2DCOR) [22,23], mowing windows 2D concept (MW2D) [24,25], factor (FA) and principal component analysis (PCA) [26][27][28][29], etc.…”
Section: Resultsmentioning
confidence: 99%
“…3). The number of the statistically significant PCs was evaluated using the factor indicator function, which reaches a minimum when the correct number of factors (components) is employed [26,32]. It was found that statistically significant can be first five PCs.…”
Section: Resultsmentioning
confidence: 99%
“…eigenvalues of the covariance or correlation matrix. Methods in this group are GAP [32], [33], RAE (ratio of adjacent eigenvalues) [34], SORTE (second order statistic of the eigenvalues) [33], [32], RAESORTE [34], and EIF (empirical indicator function) [35], [36]. Former methods estimate mode-n rank from the unfolded tensor ( ) n X by searching for dominant eigenvalues of the Gramm matrix ( ) ( ) T n n X X according to some criterion, e.g.…”
Section: Dimensions Of the Core Tensormentioning
confidence: 99%
“…The first two singular vectors interpret almost 98% of the variance leaving a marginal difference between a possible third factor and the noise in the data. Not surprisingly, a larger number of methods have been developed to extract the likely number of factors from experimental data [e.g., 3,[25][26][27]. Given the narrow margin left for decision, it is always recommended to check whether the system can be reasonably interpreted with more or less species that suggested by whatever test criterion.…”
Section: Ambiguitiesmentioning
confidence: 99%